Policy for Attacking Poverty Case: Cambodia - Vanny, Marvin; Frinaldi, Aldri; Sok, Vanny (Darul Yasin Al Sys, 2024)
What are the causes of poverty? And why is poverty so widespread in the world? To answer these frequently asked questions, there are several factors to consider when it comes to the aspects that contribute to the causes of poverty. Factors such as economic, political, institutional and cultural aspects can all influence the case. As can be seen in Cambodia, the last decade has seen significant economic growth and poverty reduction, accompanied by numerous structural policy changes. However, a significant wealth and income gap still exists between the country's lower and upper classes, while the sudden onset of the COVID-19 pandemic has devastated Cambodia and pushed many people into poverty. Additionally, rural and low-income families face challenges accessing services and jobs, necessitating the focus on improving public institutions' capacities for effective resource management and responsible service delivery. This article hopes to provide valuable information to future researchers on poverty alleviation policies in Cambodia and the factors that contribute to urban-rural poverty.